2014
DOI: 10.1105/tpc.114.126789
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule Plus-End Tracking Protein ARMADILLO-REPEAT KINESIN1 Promotes Microtubule Catastrophe in Arabidopsis

Abstract: Microtubule dynamics are critically important for plant cell development. Here, we show that Arabidopsis thaliana ARMADILLO-REPEAT KINESIN1 (ARK1) plays a key role in root hair tip growth by promoting microtubule catastrophe events. This destabilizing activity appears to maintain adequate free tubulin concentrations in order to permit rapid microtubule growth, which in turn is correlated with uniform tip growth. Microtubules in ark1-1 root hairs exhibited reduced catastrophe frequency and slower growth velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 49 publications
2
51
1
Order By: Relevance
“…Treatment of root hairs with microtubule inhibitors has been shown to lead to wavy growth and the formation of multiple growth tips (Bibikova et al, 1999). In addition, genetic analyses have demonstrated that kinesin motor proteins regulate the directionality of tip growth through microtubule organization (Eng and Wasteneys, 2014;Hiwatashi et al, 2014;Eng et al, 2017). Although longitudinal microtubules similar to those present in root hairs were observed in rhizoids (Murata et al, 1987;Corellou et al, 2005;Duckett et al, 2014), microtubule function in rhizoid growth remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of root hairs with microtubule inhibitors has been shown to lead to wavy growth and the formation of multiple growth tips (Bibikova et al, 1999). In addition, genetic analyses have demonstrated that kinesin motor proteins regulate the directionality of tip growth through microtubule organization (Eng and Wasteneys, 2014;Hiwatashi et al, 2014;Eng et al, 2017). Although longitudinal microtubules similar to those present in root hairs were observed in rhizoids (Murata et al, 1987;Corellou et al, 2005;Duckett et al, 2014), microtubule function in rhizoid growth remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the use of the motor-only construct with which we could not recapitulate the plus-end enrichment of Kinesin-13. Alternatively, considering the decrease and increase in catastrophe and rescue frequency of interphase MTs, it is possible the Kinesin-13 regulates growth and shrink rate indirectly via tubulin cycling: reduced catastrophe would result in reduced availability of tubulin in the free tubulin pool, which might affect MT growth and shrink rates, as was proposed in the studies of Arabidopsis ARK proteins (Eng and Wasteneys, 2014) and more recently with plant-specific MT nucleator MACET4 (Schmidt and Smertenko, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The interphase microtubules tend to remain laterally attached to the cell's plasma membrane and rely on cortical attachment to form and maintain functional array patterns (Dhonukshe et al, 2003;Shaw et al, 2003). While molecular mechanisms explicitly related to creating transverse patterns have not been identified in hypocotyl cells, a significant number of genes are known to alter the degree of coalignment or affect microtubule dynamics (Ambrose et al, 2007;Bisgrove et al, 2008;Motose et al, 2011;Kirik et al, 2012;Lin et al, 2013;Lindeboom et al, 2013;Oda and Fukuda, 2013;Wightman et al, 2013;Eng and Wasteneys, 2014;Galva et al, 2014;Walia et al, 2014;Takatani et al, 2017). These activities have been used as a basis for modeling the interactions of cortical array polymers that could lead to ordered states (Eren et al, 2012;Deinum and Mulder, 2013).…”
Section: Molecular Mechanisms and The Origin Of Oriented Microtubule mentioning
confidence: 99%